Leukocyte urokinase plasminogen activator receptor and PSGL1 play a role in endogenous arterial fibrinolysis - Bai, Xufang; Weitz, Jeffrey I.; Gross, Peter L. (Thrombosis and Haemostasis, 2009)
Fibrin is an integral component of arterial thrombi. Using a mouse model of arteriolar thrombosis, high-speed fluorescence microscopy reveals that, within minutes, the fibrin content of thrombi rapidly increases and then decreases.The decrease in fibrin coincides with leukocyte binding to the thrombi, a process mediated by the interaction of leukocyte P-selectin glycoprotein ligand-1 (PSGL-1) with P-selectin on the surface of activated platelets. Because leukocytes possess urokinase-type plasminogen activator (uPA) activity,we used mice deficient in uPA or the uPA receptor (uPAR) to explore the contribution of leukocyte associated uPA to the loss of fibrin from these thrombi. Fibrin loss in both uPA-deficient mice and uPAR-deficient mice was reduced compared with that in wild-type controls.Transfusion of leukocytes from wild-type mice into uPAR-deficient mice restored fibrin loss to levels similar to that in wild-type mice. In contrast, transfusion of leukocytes from mice deficient in uPAR or PSGL-1 did not enhance fibrin loss. Thus, fibrin loss from microarteriolar thrombi is mediated, at least in part, by leukocyte-associated uPA in a process that requires leukocyte uPAR and PSGL-1.
Keywords: Thrombosis; mouse models; plasmin; tissue-type plasminogen activator; urokinase-type plasminogen activator receptor